PENGARUH PELAYANAN PERPUSTAKAAN TERHADAP MINAT BACA SISWA SD - Ardiansyah Ardiansyah (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
This study aims to determine the effect of library services on elementary school students 'reading interest and how its significance. This research method uses quantitative methods with the "product moment" correlation type. The population in this study were all students of SDN Teja Barat 1 Pamekasan which are 197 students totally. The sample in this study was 60 students taken by random sampling. The size of sample is 60 students. Data collection was collected by questionnaires and interviews. Analysis of research data used "product moment" correlation analysis, which library services as the independent variable and elementary school students' reading interest as the dependent variable.The results of the study showed that: (1) There is an effect of library services on students' reading interest. It showed from the results of data analysis, that the value of "r" count 0.640 is greater than "r" table of product moment, weather in the 5% confidence interval = 0.254 or 1% = 0.330. (2) The library services influences the students' reading interest a significance contribution, that is 40.96% and the remaining 59.04% was influenced by other factors. So the increase of library services, also increasing the students' reading interest.